1275. Dynamics of Enterococcus faecalis Cardiolipin Synthase Gene Expression Reveal Compensatory Roles in Daptomycin Resistance. (4th December 2021) - Nguyen, April; Polamraju, Vinathi; Zhang, Rutan; Tran, Truc T; Panesso, Diana; Khan, Ayesha; Mileykovskaya, Eugenia; Shamoo, Yousif; Xu, Libin; Vitrac, Heidi; Arias, Cesar A
Abstract: Background: Daptomycin (DAP) is a lipopeptide antibiotic targeting membrane anionic phospholipids (APLs) at the division septum, and resistance (DAP-R) has been associated with activation of the E. faecalis (Efs ) LiaFSR response and redistribution of APL microdomains (predicted to contain cardiolipin) away from the septum. Efs encodes two putative cardiolipin synthase genes, cls1 and cls2 . While changes in Cls1 are associated with DAP-R, the exact roles of each enzyme in resistance are unknown. This work aims to establish the contributions for both enzymes in the development of DAP-R. Methods: cls1 and cls2 were deleted individually and in tandem from Efs OG117∆ liaX (a DAP-R strain with an activated LiaFSR response). Mutants were characterized by DAP minimum inhibitory concentration (MIC) using E-test and localization of APL microdomains with 10-N-nonyl-acridine orange staining. Quantitative PCR (qRT-PCR) was used to study gene expression profiles of cls1 and cls2 in Efs OG117∆ liaX relative to Efs OG117. Membrane lipid content was analyzed using hydrophilic interaction chromatography-mass spectrometry (HILIC-MS). Results: cls1 was highly upregulated in stationary phase concurrent with a decrease in cls2 expression. However, independent deletion of cls1 or cls2 in the DAP-R background resulted in no significant phenotypic changes from the parent strain. Interestingly, qRT-PCR showed that cls2 expression was upregulated upon deletion of cls1 (and vice-versa), suggesting a compensatory role for one enzyme upon deletion of the other (Fig 1). When comparing membrane lipid content between Efs OG117∆ liaX ∆ cls1 and Efs OG117∆ liaX ∆ cls2, there were no significant differences in both the overall amount or species of cardiolipin generated, further supporting a potential redundancy between the cardiolipin synthases (Fig 2). Ultimately, double deletion of both cls genes lowered the DAP MIC relative to the parent strain and restored septal localization of APL microdomains. Conclusion: Overall, Cls1 has a predominant role in the development of DAP-R in E. faecalis . However, here, we describe a novel compensatory role for Cls2 under conditions in which there is no functional Cls1 to maintain the DAP-R phenotype. Disclosures: Truc T. Tran, PharmD, Merck (Grant/Research Support) Cesar A. Arias, M.D., MSc, Ph.D., FIDSA, Entasis Therapeutics (Grant/Research Support)MeMed Diagnostics (Grant/Research Support)Merk (Grant/Research Support)